Resiliensi Mahasiswa Korban Toxic Relationship - Pingkan R. N Sahabang; Shanti N. Ch. Ruata; Fienny M. Langi (Institut Agama Kristen Negeri Manado, 2023)
The background of this research is that there are students at IAKN Manado who have experienced unhealthy relationships or are said to be in toxic relationships. The purpose of this study is to identify how the resilience of students who are victims of toxic relationships, along with efforts to build resilience after a toxic relationship occurs. This study uses a qualitative method with a case study approach. This research was conducted on 3 students at the IAKN Manado campus, with data collection techniques through observation, interviews, and documentation. In this study the researchers got the results that proved that there was a toxic relationship phenomenon among the three students on the Manado IAKN campus, these three students had experienced physical and verbal violence and were not released in carrying out activities, for example in lectures, social activities such as spiritual activities, and also in a friendship environment, thus making these students experience pressure and stress.